Adopting additive manufacturing in SMEs: exploring the challenges and solutions. Issue 6 (15th October 2018) - Martinsuo, Miia; Luomaranta, Toni
Abstract : Purpose: Adopting additive manufacturing (AM) can be challenging, especially in small- and medium-sized enterprises (SMEs) and as part of the supply chains of larger firms. The purpose of this paper is to explore SMEs' perspectives on the adoption of AM in their specific supply chain positions. The paper develops new knowledge on the challenges SMEs face across the supply chain and the actions they need to promote the adoption of AM. Design/methodology/approach: An exploratory interview-based research design is used. In total, 17 interviews were conducted and analyzed in four types of SMEs in their specific positions in AM supply chains. The challenges of adopting AM were mapped, and actions to promote AM adoption were identified. Findings: SMEs in different supply chain positions experience different challenges when adopting AM. Strategic and operative actions are suggested as key solutions to overcome the challenges. The benefits of AM on a large scale will be achieved only if the broader supply chain adopts AM technology and experiences its benefits. Research limitations/implications: The research is limited by its single-country context, its focus on SMEs, and the selection of early-phase AM-adopter firms. The findings imply a need to understand AM adoption as a shared concern and systemic innovation in the supply chain, instead of just a firm-specific implementation task. Practical implications: The findings offer a framework for categorizing AM adoption challenges and propose ways to overcome the challenges of adoption. Originality/value: The study reveals that AM adoption is not only a technology issue, but also an issue of strategic, organizational and operational challenges across the supply chain. It shows that when adopting AM, SMEs face particular challenges and require specific solutions according to their supply chain position.